Protecting Landowner Rights: Enforcement of Criminal Law Against Land Encroachment in Indonesia - Ardini, Aida; Hasibuan, Muhammad Ibrahim; Ummairah, Dinda; Anugerah Putri, Edselin Queen (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
This study comprehensively explores the application of Indonesian positive law in addressing cases of unauthorized land encroachment, specifically focusing on the legal actions taken against individuals who unlawfully occupy land without the owner’s consent. The primary objective of this research is to analyze the legal framework governing land encroachment in Indonesia, as well as to understand the penalties and legal consequences imposed on individuals found guilty of such acts. Employing a normative legal research method, this study conducts an extensive literature review of relevant legal articles, focusing on Law No. 5/1960 and the Indonesian Criminal Code. Three central research questions guide this investigation: first, the legal definition and classification of land encroachment as outlined in Indonesian positive law; second, the scope and nature of criminal sanctions applicable to those found guilty of unauthorized occupation or trespass on another person’s property; and third, the specific mechanisms and processes for law enforcement, including administrative and judicial procedures, used to address and mitigate instances of land encroachment in Indonesia. Through this study, we aim to provide a clearer understanding of how existing legal provisions are enforced to protect landowners' rights and maintain public order in relation to land ownership and use. This research also seeks to contribute to the broader discourse on land rights and legal protections in Indonesia, shedding light on potential areas for policy enhancement to ensure effective legal recourse for land encroachment cases.